Depression and Breast Cancer in Morocco: Prevalence and Associated Factors - Khadija Benallel; Rajae El Kilali; Roukaya Benjelloun; Mohamed Kadiri (International Journal of Breast Cancer)
Background. Depression is frequently associated with breast cancer. However, its prevalence and impact on patients’ quality of life are negligible. Depression is often underdiagnosed and less treated. Objectives. Our study is aimed at estimating the prevalence of depression in breast cancer patients, describing their sociodemographic and clinical profile, and determining the factors associated with this depression. Material and Methods. We carried out a cross-sectional, descriptive, and analytical study, conducted from January to March 2018 at Mohammed V Military Hospital in Rabat. The survey included 100 breast cancer patients. It was conducted using an anonymous questionnaire, the Mini International Neuropsychiatric Interview test (MINI test) to diagnose depression and the Beck Depression Inventory (BDI) to assess its severity. Results. The major depressive episode was diagnosed in 26% of breast cancer patients. Age under 40, psychiatric history, metastatic breast cancer, refusal of treatment, heavier treatment, and spousal alteration were the factors most associated with higher depression prevalence in these patients. Discussion and Conclusion. The high prevalence of depression in breast cancer patients, as well as the influence of personal characteristics and treatment in the occurrence of this ailment, has been confirmed by several authors. It is recommended to improve the psychooncological care of patients with breast cancer, to prevent the occurrence of depression in this vulnerable population.